الخلايا الشّمسيّة واستخدامها في عناصر الفرش العمراني لرفع أداء الحدائق العامّة - لمى ونّوس (Tishreen University, 2019)
تشكّل الحدائق العامّة أحد المكوّنات الرّئيسيّة للمدن، حيث تمثّل الرّئة الأساسيّة للتنّزّه وقضاء أوقات الفراغ للوصول إلى مستوى وأداء معيشيّ أفضل للسّكّان، فهي تعمل على حماية الموارد الطّبيعيّة والبيئيّة وتحسين ظروف البيئة، وخاصّةً في ظلّ المرحلة الحاليّة الّتي تشهد الكثير من التّحديّات البيئيّة ، وأهمّها نضوب الطّاقات الأحفوريّة ، والبحث عن الحلول المناسبة للتّوفير في الطّاقة وحماية البيئة، ممّا شجّع على استخدام الطّاقات النّظيفة وخاصّةً الطّاقة الشّمسيّة الّتي تنعكس تقنيّاتها في مختلف مجالات الحياة، وكان لا بدّ أن يؤخذ بعين الاعتبار الاهتمام بتصميم الحدائق العامّة واستخدام الطّاقة الشّمسيّة في عناصر فرشها العمرانيّ، لإيجاد بيئة ملائمة تحقّق التّفاعل بين الإنسان ومحيطه. وتشكّل عناصر الفرش العمرانيّ للحدائق المكوّن الأساسي لها، الّذي يعطي الهويّة الجماليّة والعمليّة لتلك الحدائق، وانعكاس ذلك على أفراد المجتمع، فظهرت الحاجة إلى ضرورة تطوير هذه العناصر باستخدام الخلايا الشّمسيّة لرفع أداء الحدائق العامّة بما يخدم الإنسان ومتطلّباته ويساعد على حماية البيئة ،من خلال التّوفير في استهلاك الطّاقة، وتحقيق التّفاعل الاجتماعي الفعلي والالكتروني. Public parks form one of the main components for cities  ,that represent  the basic patch for hiking and spending spare times in order to reach a better level and living  performance for population, It  works on protecting the natural and environmental  resources and make the environment conditions better , especially in the current stage that witnesses a lot of environment challenges,  which is the most important of it is depletion of fossil energy , and searching for the appropriate solutions in saving energy and environment protection , which  encourage  using the clean energies specially solar power that its techniques reflected in different life fields , and we have to take in our considerations taking care  of the designs of public parks and using solar power in its  urban brushes in order to find a suitable environment that make the interaction between human and his ambience . The elements of the urban brushes for parks form the basic components of it , that gives the aesthetic and practical  identity  for these parks and its reflected on society members ,so the necessity of develop  these elements by using solar cells appeared  to raise up the parks performance , that serve human and his needs , also working on protecting  the environments by  saving energy consuming and achieving social and electronic  interaction